Cambrian stem-group ambulacrarians and the nature of the ancestral deuterostome - Li, Y; Dunn, FS; Murdock, DJE; Guo, J; Rahman, IA; Cong, P (Cell Press, 2023)
Deuterostomes are characterized by some of the most widely divergent body plans in the animal kingdom. These striking morphological differences have hindered efforts to predict ancestral characters, with the origin and earliest evolution of the group remaining ambiguous. Several iconic Cambrian fossils have been suggested to be early deuterostomes and hence could help elucidate ancestral character states. However, their phylogenetic relationships are controversial. Here, we describe new, exceptionally preserved specimens of the discoidal metazoan Rotadiscus grandis from the early Cambrian Chengjiang biota of China. These reveal a previously unknown double spiral structure, which we interpret as a chordate-like covering to a coelomopore, located adjacent to a horseshoe-shaped tentacle complex. The tentacles differ in key aspects from those seen in lophophorates and are instead more similar to the tentacular systems of extant pterobranchs and echinoderms. Thus, Rotadiscus exhibits a chimeric combination of ambulacrarian and chordate characters. Phylogenetic analyses recover Rotadiscus and closely related fossil taxa as stem ambulacrarians, filling a significant morphological gap in the deuterostome tree of life. These results allow us to reconstruct the ancestral body plans of major clades of deuterostomes, revealing that key traits of extant forms, such as a post-anal region, gill bars, and a U-shaped gut, evolved through convergence.